Location Evaluation of Bicycle Sharing System Stations and Cycling Infrastructures with Best Worst Method Using GIS. Issue 3 (3rd July 2021) - Guler, Dogus; Yomralioglu, Tahsin
Abstract : Bicycle sharing systems (BSSs) in urban areas are considered an effective solution for enabling sustainable transportation. In this sense, the locations of BSS stations (BSSSs) are of vital importance to establish efficient BSSs. In addition, citizens should be able to benefit from suitable cycling infrastructure (CI) for their safety. For this reason, the aim of this article is to propose an integrated framework that includes the best worst method (BWM) and geographic information systems (GIS) techniques to determine optimal locations of BSSSs and CIs simultaneously. Proposed BSSS locations and CIs are ranked to present more elaborate results. Moreover, sensitivity analysis is applied with the aim of revealing the uncertainty in the model. In this connection, the locations close to shorelines are found to be highly suitable, because they have advantages in terms of important criteria such as BSSS and transportation station. Consequently, this study presents the interplay of GIS techniques and multicriteria decision making methods, offering a significant solution for simultaneous location selection of BSSS and CI. The results of the approach proposed in this article can be used as a basis for both transportation planning and urban planning.